Sodium-glucose cotransporter-2 inhibitor for renal function preservation in patients with type 2 diabetes mellitus: A Korean Diabetes Association and Korean Society of Nephrology consensus statement - Tae Jung Oh; Ju-Young Moon; Kyu Yeon Hur; Seung Hyun Ko; Hyun Jung Kim; Taehee Kim; Dong Won Lee; Min Kyong Moon; The Committee of Clinical Practice Guideline, Korean Diabetes Association and Committee of the Cooperative Studies, Korean Society of Nephrology (The Korean Society of Nephrology, 2020)
Diabetes is a leading cause of end-stage renal disease. Therefore, prevention of renal dysfunction is an important treatment goal in the management of diabetes. The data of landmark cardiovascular outcome trials of sodiumglucose cotransporter-2 (SGLT2) inhibitors showed profound reno-protective effects. The Korean Diabetes Association and the Korean Society of Nephrology reviewed clinical trials and performed a meta-analysis to assess the effects of SGLT2 inhibitors on the preservation of estimated glomerular filtration rate (eGFR). We limited the data of SGLT2 inhibitors which can be prescribed in Korea. Both eGFR value and its change from the baseline were significantly more preserved in the SGLT2-inhibitor treatment group compared to the control group after 156 weeks. However, some known adverse events were increased in SGLT2 inhibitor treatment, such as genital infection, diabetic ketoacidosis, and volume depletion. We recommend long-term use of SGLT2 inhibitors in patients with type 2 diabetes mellitus (T2DM) for attenuation of renal function decline. However, we cannot generalize our recommendations due to the lack of long-term clinical trials testing the reno-protective effects of every SGLT2 inhibitor in a broad range of patients with T2DM. This recommendation can be revised and updated after the publication of several large-scale renal outcome trials.